Academic Librarian Collaborations in Inquiry Based Learning: A Case Study, Reflections and Strategies - Murphy, James E.; Koltutsky, Laura; Lenart, Bartlomiej; McClurg, Caitlin; Stoeckle, Marc (Partnership, 2020)
Five academic librarians at the University of Calgary were invited to collaborate on an inquiry-based learning course. Each librarian represented different liaison responsibilities and expertise and was paired with a course section of primarily first-year students, an instructor, and a teaching assistant. The range of experiences among the librarians provided insights into issues of library partnerships, embedded librarianship, and information literacy instruction. Benefits of the collaboration included opportunities for instruction, positive student perceptions, skill building, and teaching innovations, while areas for further development included sustainability and role definition. Proposed areas of future growth include quantitative exploration of librarian involvement in inquiry- based learning.